2016
DOI: 10.1177/1078155215616278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the appropriateness of a community pharmacy model for a colorectal cancer screening program in Catalonia (Spain)

Abstract: Background The traditional model of community pharmacy has changed, with patients, caregivers and consumers having access to many cognitive services other than the traditional dispensing and supply of medicines. In December 2009, a population-based colorectal cancer screening program started in Barcelona, introducing the community pharmacist and the professional expertise of the pharmacist into the organisational model. Aim To evaluate the program implementation process in the pharmacies, identify barriers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…32,46 Recent studies have evaluated the role of pharmacy-based CRC screening interventions and the impact of community pharmacist as the first line in CRC risk counselling and screening. 22,45,47 In these studies, pharmacists have shown high levels of attitudes, satisfaction and motivation in participation of different CRC screening interventions and to act as the role model in delivering many cognitive services beyond drug dispensing particularly providing home FOBT to eligible patients as well as CRC screening education. Collectively, these studies indicate that positive attitude of pharmacists could be reflected on public involvement in CRC screening initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…32,46 Recent studies have evaluated the role of pharmacy-based CRC screening interventions and the impact of community pharmacist as the first line in CRC risk counselling and screening. 22,45,47 In these studies, pharmacists have shown high levels of attitudes, satisfaction and motivation in participation of different CRC screening interventions and to act as the role model in delivering many cognitive services beyond drug dispensing particularly providing home FOBT to eligible patients as well as CRC screening education. Collectively, these studies indicate that positive attitude of pharmacists could be reflected on public involvement in CRC screening initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists perceive this role to be important because they recognise the need for increased cancer screening, feel they can influence consumers to engage in screening and believe consumers appreciate this service 26-29. Pharmacists consider the promotion of cancer screening to add value to their role, and to increase consumers’ confidence in them as health professionals 30…”
Section: Discussionmentioning
confidence: 99%
“…In Netherland the introduction of FIT test enclosed within the invitation mailed results in the participation rate above 65% (Toes-Zoutendijk et al, 2017). Implication of pharmacists have also been shown to be a successful alternative, with good results in terms of participation and sustainability of the whole process (Mancini et al, 2016) (Santolaya et al, 2017).…”
Section: Diversifying Approachesmentioning
confidence: 99%